Further observations of a decreasing atmospheric CO2 uptake capacity in the Canada Basin (Arctic Ocean) due to sea ice loss. Issue 6 (25th March 2013) - Else, Brent G.T.; Galley, R.J.; Lansard, B.; Barber, D.G.; Brown, K.; Miller, L.A.; Mucci, A.; Papakyriakou, T.N.; Tremblay, J.‐É.; Rysgaard, S.
Abstract: [1] Using data collected in 2009, we evaluated the potential for the southeastern Canada Basin (Arctic Ocean) to act as an atmospheric CO2 sink under the summertime ice‐free conditions expected in the near future. Beneath a heavily decayed ice cover, we found surprisingly high p CO2sw ( 290–320 µatm), considering that surface water temperatures were low and the influence of ice melt was strong. A simple model simulating melt of the remaining ice and exposure of the surface water for 100 days revealed a weak capacity for atmospheric CO2 uptake (mean flux: −2.4 mmol m −2 d −1 ), due largely to warming of the shallow mixed layer. Our results confirm a previous finding that the Canada Basin is not a significant sink of atmospheric CO2 under summertime ice‐free conditions and that increased ventilation of the surface mixed layer due to sea ice loss is weakening the sink even further. Key Points: The southeastern Canada Basin has a weak capacity to absorb atmospheric CO2 A shallow mixed layer that warms rapidly after ice loss inhibits CO2 uptake Ice‐free summers in the Canada Basin will not create a significant new CO2 sink